Pengaruh Koneksi Politik dan Keragaman Gender terhadap Agresivitas Pajak - Adzkia Celina Asmara; Herlina Helmy (Universitas Negeri Padang, 2023)
This study aims to determine the effect of Political Connections and Gender Diversity on tax aggressiveness. The company uses tax aggressiveness to fulfill tax obligations that do not violate tax regulations and do not conflict with laws. The reduction in the tax burden is the main reason for companies to carry out tax aggressiveness. This research is a type of quantitative research. The research sample is mining sector companies listed on the IDX for the 2018-2020 period. This research sample selection method is using purposive sampling method. Secondary data is obtained based on the annual financial reports on the IDX. The results of the study show that political connections have a negative effect on tax aggressiveness and gender diversity has a negative effect on tax aggressiveness. This research contributes to the government being able to improve supervision of companies that have close relationships so that they remain compliant in paying taxes and avoid tax risks.